A single amino acid substitution in the MurF UDP‐MurNAc‐pentapeptide synthetase renders Streptococcus pneumoniae dependent on CO2 and temperature. Issue 3 (28th June 2013) - Burghout, Peter; Quintero, Beatríz; Bos, Linda; Beilharz, Katrin; Veening, Jan‐Willem; de Jonge, Marien I.; van der Linden, Mark; van der Ende, Arie; Hermans, Peter W. M.
Summary: The respiratory tract pathogen Streptococcus pneumoniae encounters different levels of environmental CO2 during transmission, host colonization and disease. About 8% of all pneumococcal isolates are capnophiles that require CO2 ‐enriched growth conditions. The underlying molecular mechanism for caphnophilic behaviour, as well as its biological function is unknown. Here, we found that capnophilic S. pneumoniae isolates from clonal complex (CC) 156 (i.e. Spain 9V ‐3 ancestry) and CC344 (i.e. Norway NT ‐42 ancestry) have a valine at position 179 in the MurF UDP‐MurNAc‐pentapeptide synthetase. At ≤ 30°C, the growth characteristics of capnophilic and non‐capnophilic CC156 strains were equal, but at > 30°C growth and survival of MurF V 179 strains was dependent on > 0.1% CO2 ‐enriched conditions. Expression of MurF V 179 in S. pneumoniae  R6 and G54 rendered these, otherwise non‐capnophilic strains, capnophilic. Time‐lapse microscopy revealed that a capnophilic CC156 strain undergoes rapid autolysis upon exposure to CO2 ‐poor conditions at 37°C, and staining with fluorescently labelled vancomycin showed a defect in de novo cell wall synthesis. In summary, in capnophilic S. pneumoniae strains from CC156 and CC344 cell wall synthesis is placed under control of environmental CO2 levels and temperature. This mechanism might represent a novel strategy of the pneumococcus to rapidly adapt and colonize its host under changing environmental conditions.